(untitled) (GIST – Education and Learning Research Journal, 2013)
Many of the actions of Colombia’s National Programme for the Development of Foreign Languages (Programa Nacional de Desarrollo de Lenguas Extranjeras – PNDLE) have been carried out in elementary and secondary education, but there is not much information about its impact in institutions of higher education. The aim of this article is to present the initiatives taken as well as the challenges faced by the Languages Department in order to foster bilingualism at Universidad Central in Bogota, Colombia. To explain the reasons behind these initiatives, quality indicators for successful bilingual programs were used and the situation at the university in comparison to the indicators is described. It is concluded that the endeavour of graduating bilingual students will not be easy to achieve unless institutions incorporate models of bilingual education as indicators for accreditation and support the labours of languages departments.